Panorama hidrotermal argentino - Sabatte, José Antonio (Anales de Hidrología Médica, 2008)
The descriptive work deals with two aspects of Argentine spas: their historical forerunners since pre-Columbian times and their different climactic and bioclimatic conditions, as the spas of the Republic are scattered throughout the territory in very different regions.
Keywords: Thermalism; Health Tourism; Balneology; Thermal Waters